PENGETAHUAN TRADISIONAL MASYARAKAT DALAM BUDIDAYA TANAMAN KELAPA DI DESA TINDOI KECAMATAN WANGI-WANGI KABUPATEN WAKATOBI - Nesti Werdiani; Dasmin Sidu; Mardin Mardin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
This study aims to determine the traditional knowledge of the community in coconut cultivation in Tindoi Village, Wangi-Wangi District, Wakatobi Regency. The number of respondents in this study were 6 people who were determined using the snowball technique. The results of this study shows that: (1) Land provision for coconut cultivation does not arbitrarily chosen by the community in Tindoi Village Wangi-Wangi District Wakatobi Regency,Kaindea forest and Padangkuku forest are options the main community in the cultivation of coconut plants. (2) Tindoi Village community usually clearing forest land is done first slashing shrubs but before slashing the community first in the past, reading a mantra or prayer, the people there used to call it designation Batata. (3) Provision of coconut seeds by the Village community Tindoi, namely coconut seeds, can be directly taken from the mother tree, which is healthy and good. (4) The people of Tindoi Village before planting coconut first of all, you have to determine the good day,which is the good day is on yhe full moon that the people of Tindoi Village call it as Komba Ompulu Lolima which has the largest moon meaning of the moon another month.(5) The people of Tindoi Village have traditional knowledge in planting coconuts, namely in the process of planting coconuts must be male and planting during the day.When diong one has to sit on the ground and one has to carry one child behind him. (6) The people of Tindoi Village use coconut dregs or what they call kosea as fertilizer. Coconut or kosea dregs this is obtained from the juice of coconut milk and they use it as fertilizer usually they throw the kosea or coconut dregs to the coconut plant.